Improving adolescent mental health through spiritual coping using MCHC application - Dwidiyanti, Meidiana; Wijayanti, Diyan Yuli; Mu’in, Muhammad; Dewi, Nur Setiawati; Nurrahima, Artika; Hartati, Elis (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Background: Family is one of the factors that influence adolescent mental health. Adolescents often have problems with closeness to parents, communication, openness, and support, and those with poor mental health can be at risk for self-harm. One of the coping methods that can be used to increase the interaction between parents and adolescents is spiritual coping.Purpose: This study aimed to determine differences in the level of mother-adolescent interaction and its effect on adolescent mental health after the application of spiritual coping interventions.Methods: A quantitative study using a pretest-posttest quasi-experimental design with a control group was conducted among 52 public health volunteers and their adolescent children. This study described data of two groups before and after spiritual coping interventions through the Mother and Child Heart Connection (MCHC) Caring System. The Parent-Child Interaction Questionnaire-Revised (PACHIQ-R) and Mental Health Inventory (MHI) questionnaires were used for data collection.Results: The results of the independent t-test showed a sig. value of 0.036 (p0.05), indicating a significant difference in the level of interaction and mental health between the intervention group and the control group before and after the intervention.Conclusion: The application of spiritual coping interventions through the MCHC application positively affected the interaction between mothers and adolescent children. Spiritual coping increased the acceptance and awareness of mothers that could improve their interaction and mental health condition of adolescents.